2020
DOI: 10.1101/2020.07.15.203059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Famotidine on SARS-CoV-2 Proteases and Virus Replication

Abstract: The lack of coronavirus-specific antiviral drugs has instigated multiple drug repurposing studies to redirect previously approved medicines for the treatment of SARS-CoV-2, the coronavirus behind the ongoing COVID-19 pandemic. A recent, large-scale, retrospective clinical study showed that famotidine, when administered at a high dose to hospitalized COVID-19 patients, reduced the rates of intubation and mortality. A separate, patient-reported study associated famotidine use with improvements in mild to moderat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Given Ub–AMC is cleaved more efficiently by PLpro, the inhibitory effect of ebselen might be more pronounced when using Ub–AMC as substrate. Our result on famotidine is consistent with a recently study showing that famotidine neither inhibit the activity of PLpro nor the replication of SARS-CoV-2 in cells 36 , 37 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Given Ub–AMC is cleaved more efficiently by PLpro, the inhibitory effect of ebselen might be more pronounced when using Ub–AMC as substrate. Our result on famotidine is consistent with a recently study showing that famotidine neither inhibit the activity of PLpro nor the replication of SARS-CoV-2 in cells 36 , 37 .…”
Section: Resultssupporting
confidence: 93%
“…Famotidine is a histamine receptor antagonist which was proven to mitigate COVID-19 disease in clinics 33 , 34 . Famotidine was predicted to target the catalytic site of PLpro in a in silico screening of the licensed compound libraries 33 , 35 ; however, in the following experimental study, famotidine neither binds nor inhibits the PLpro 36 , 37 . Ebselen has therapeutic activity in neurological disorders, bipolar disorders and hearing loss 38 , 39 , 40 , and it was recently shown that the drug is potent against PLpro and has anti-SARS-CoV-2 activity 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Malone and colleagues demonstrated that famotidine did not inhibit SARS-CoV-2 infection in Vero E6 cells nor did it inhibit PL pro [43]. Loffredo et al failed to show, any significant effect of famotidine on protease function and SARS-CoV-2 replication when tested in A549 and Vero E6 cell lines [51].…”
Section: Experimental Data Examining Histamine Receptor Antagonists Amentioning
confidence: 99%
“…The nucleocapsids assembled from gRNA encapsidated by N protein and the structural proteins S, E and M inserted in the endoplasmic reticulum move along the secretory pathway (➐) and form mature virions that are transported to the cell surface in vesicles (➑) and released from the infected cell by exocytosis (➒) [7,10,11]. Bold arrows indicate the sites of action of the histamine H 2 receptor antagonist famotidine as proposed by computational studies [5,36,40], yet not experimentally confirmed [43,51] the investigational nucleotide analog remdesivir that has shown broad antiviral activity and is under clinical evaluation for the treatment of COVID-19 [13,14]. De novo drug development, drug repurposing and natural product screening are also directed at the essential proteases for viral replication [5], PL pro [6,15] and 3CL pro , which cleaves itself and, by cleaving pp1ab at 11 canonical sites (between nsps), it generates nsp4-16 and mediates their maturation [16].…”
Section: Sars-cov-2mentioning
confidence: 99%
“…DMSO served as a negative control. Forty-eight hours later, the cells were fixed in 4% paraformaldehyde and processed for immunofluorescence as previously described ( Loffredo et al, 2020 ). The cytotoxicity of GRL-0496 was measured by the CellTiter-Glo luminescent cell viability assay (Promega, Wisconsin, USA, #G7570).…”
Section: Methodsmentioning
confidence: 99%